Cobertura e depósito de calda fitossanitária em plantas de café pulverizadas com equipamento original e adaptado para plantas altas - Ferreira, Marcelo da Costa [UNESP]; Leite, Gilson José [UNESP]; Lasmar, Olinto [UNESP] (My University, 2013)
The objective of this study was to evaluate the coverage of spray droplets on coffee plants as well as their deposition using a sprayer with and without adaptation of an auxiliary branch for tall plants. The experiment was conducted following a randomized block design with six treatments and four replications to evaluate the percentage of coverage for the spraying liquids in water sensitive paper fixed at four quadrants and two heights (lower and upper) of the plants, and the spray deposit with metallic marker (MnSO4) on sheets in the same positions of the water sensitive paper in two spray volumes (450 and 750 L h-1). The experiment was conducted in October 2011 in the town of Patrocínio-MG, and the experimental plots consisted of 30 plants of Catuaí IAC-99, with approximately 12 years of age and average height of 3.50 meters. The experiments were conducted following a randomized block design with six treatments and four replications to evaluate the coverage and deposition, in two spray volumes (450 and 750 L ha-1). Leaves were collected in four positions and also at the top four in the lower canopy. The results of the evaluations were analysed statistically by F test and for comparison of means by Tukey test at 5% probability. The auxiliary branch installed at the rear of the equipment is the most suitable when compared to use of equipment without this feature or installed in the front of the equipment. Furthermore, the application volume of 450 L ha-1 results in coverages and deposits of spraying liquids equivalents to volume of 750 L ha-1, considered sufficient according to the parameters evaluated.
Coverage and deposition of spraying liquids in coffee plants sprayed with original equipment and adapted to tall plants
Keywords: Application technology; Coffea arabica; Development; Spray